The City of Tshwane Agri-parks initiative as a case study for the sustainable intensification of smallholder agriculture in South Africa - Van der Laan, Michael (University of Pretoria, 2024)
Dissertation (MSc (Agric) Agronomy))--University of Pretoria, 2023.